THE DANGERS WAITING TO POUNCE ON HOLIDAY. (29th November 2012) - Mantoan, L; Mirfenderesky, M; Wansbrough-Jones, M; Al-Memar, A
Abstract : Typical Cat Scratch Disease is a syndrome of isolated lymphadenopathy and fever caused by the gram-negative bacillus Bartonella henselae, whose major reservoir is cats. In rare cases, Bartonella causes neurological complications. Thought to be mainly a disease of children, it is now more commonly recognized in adults. We report a 54-year-old woman, who presented to the Emergency Department with a 24-h history of difficulties in word-finding, writing and the sudden use of inappropriate words. Three weeks before she had suffered a short-lived systemic illness with fever and night sweats, followed by the development of a painful massive inguinal lymphadenopathy. She had just returned from Montenegro, where on her travels she remembered having been scratched by a wild kitten. On examination she had right and left hemispheric cognitive dysfunction with no focal neurology. Imaging of the brain, cerebrospinal fluid analysis and an EEG were normal. The diagnosis of neurobartonellosis was confirmed by a positive molecular test (16S PCR) from lymph node aspirate and positive serology. All symptoms improved with intravenous gentamicin and oral doxycycline. Central nervous system involvement is an uncommon but treatable complication of infection with Bartonella species, which can present in adults. Neurobartonellosis should be considered in patients presenting with central nervous system signs and massive lymphadenopathy and a careful history of exposure to cats is recommended in patients presenting with any unexplained encephalopathy.